Current Trends in Clinical Trials of Prodrugs - Boreski, Diogo [UNESP]; Schmid, Valentine Fabienne; Bosquesi, Priscila Longhin [UNESP]; dos Santos, Jean Leandro [UNESP]; Scarim, Cauê Benito [UNESP]; Reshetnikov, Viktor; Chin, Chung Man [UNESP] (MDPI, 2025)
The development of new drugs is a lengthy and complex process regarding its conception and ideation, passing through in silico studies, synthesis, in vivo studies, clinical trials, approval, and commercialization, with an exceptionally low success rate. The lack of efficacy, safety, and suboptimal pharmacokinetic parameters are commonly identified as significant challenges in the discovery of new drugs. To help address these challenges, various approaches have been explored in medicinal chemistry, including the use of prodrug strategies. As a well-established approach, prodrug design remains the best option for improving physicochemical properties, reducing toxicity, and increasing selectivity, all while minimizing costs and saving on biological studies. This review article aims to analyze the current advances using the prodrug approach that has allowed the advance of drug candidates to clinical trials in the last 10 years. The approaches presented here aim to inspire further molecular optimization processes and highlight the potential of this strategy to facilitate the advancement of new compounds to clinical study phases.
Keywords: clinical trials; drug discovery; prodrug design; prodrugs